Do empowered beliefs fuel effective learning? Exploring how self-efficacy mediates the path from perceived social support to self-regulated learning in Islamic boarding school context - Affandi, Ghozali Rusyid; Hadi, Cholichul; Nawangsari, Nur Ainy Fardana; Laili, Nurfi; Widyastuti (Insight: Jurnal Ilmiah Psikologi, 2023)
Student in Islamic Boarding School not only get general material, but also get religious material, so the learning model in Islamic Boarding School is very dense and is required to learn independently. Therefore, psychological capacity is needed in the form of self-regulation ability or called self-regulated learning. This study aims to determine whether self-efficacy can mediate the relationship between perceived social support and self-regulated learning of student at the Islamic Boarding School An-Nur Sidoarjo after the Covid-19 Pandemic. This study uses a quantitative method with a cross-sectional study type. The population in this study were students at the Islamic Boarding School An-Nur Sidoarjo aged 12-15 with a total of 194 students. The sample size was 194 students using saturated sampling technique. Data collection tools consist of 3 psychological scales, namely Self Efficacy Questionnaire for Children (SEQ-C), Multidimensional Scale of Perceived Social Support (MSPSS), and The Short Self-Regulation Questionnaire for Taiwanese College Students (TSSRQ) to detect self-regulated learning. Data analysis used in the study was structural equation modelling with JASP 0.16.20 software. The analysis showed that self-efficacy is a partial mediator in the relationship between perceived social support and self-regulated learning in students at An-Nur Islamic Boarding School Sidoarjo. Research implications will be discussed.